Phase noise in signal sources theory and applications - Robins, W. P. (Institution of Engineering and Technology, 1984)
This book contains a thorough treatment of phase noise, its relationship to thermal noise and associated subjects such as frequency stability. The design of low phase noise signal sources, including oscillators and synthesisers is explained and in many cases the measured phase noise characteristics are compared with the theoretical predictions. Full theoretical treatments are combined with physical explanations, helpful comments, examples of manufactured equipment and practical tips.